PENGARUH LATIHAN ZIG-ZAG DENGAN BOLA TERHADAP KETERAMPILAN DRIBBLING PADA SSB PANCASONA ABADI TUALANG U-17 - Pratama, M. Nanda; Sulastio, Agus; Aspa, Agus Prima (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: The purpose of this research is to find out how much influence Zig-Zag training with a ball has on Dribbling Skills at the SSB Pancasona Abadi TualangU-17 Club. Research location in the SSB Pancasona Abadi Tualang Perawang field.From 7 January to 24 February 2024, the data source is SSB Pancasona Abadi TualangU-17 student players who are registered and actively participating in training. Tocollect the data needed for this research, the Dribbling Zig-Zag instrument was used.Based on the results of the research discussion above, it can be concluded that there isan influence of Zig-zag Dribbling training (X) on the endurance ability (Y) ofPancasona Abadi Tualang U-17 players. The obstacles that researchers face in the fieldafter conducting research are unpredictable weather, sometimes hot and rainy.However, researchers still continue research according to conditions in the field. Thismeans that when it rains the researcher stops the testee and continues if the field theresearcher is using is not hampered. If there are problems in the field, the researcherstops the research and continues the next day, perhaps that is the only problem in thefield that the researcher faces during the exercise.Keywords: Influence, Zig-Zag Practice, Dribbling Skills